Defending Palestine: typologies of agency among actors of the Indonesian Council of Ulama - Yanuardi Syukur (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2026)
The role of religious actors in shaping transnational solidarity is often overlooked in state‑centric analyses of international relations. This article addresses this gap by examining the typologies of agency among actors of the Indonesian Council of Ulama (MUI) in defending Palestine. Using a qualitative‑interpretative approach, the research analyses MUI’s fatwas, public statements, and actions, alongside ethnographic observations from the “Safari Ramadhan: Membasuh Luka Palestina” program. Drawing on Ortner’s concept of power and project agency, Vorhölter’s understanding of agency as socio-culturally mediated capacity, Talal Asad’s notion of Islam as a discursive tradition, and related debates in the anthropology of Islam, the findings reveal three interconnected typologies of agency: First, moral-theological agency enables MUI actors to transform political solidarity into a sacred obligation through the fatwa on fard kifayah (communal obligation). Second, relational-historical agency allows them to activate shared historical memory, anti-colonial narratives, and the symbolic centrality of Al-Aqsa to construct transnational solidarity. Third, practical-strategic agency enables them to navigate geopolitical uncertainty and materialise solidarity through humanitarian programs, grassroots mobilisation, digital activism, and boycotts. The study contributes to the anthropology of religion by showing how religious actors exercise multiple forms of agency in building transnational solidarity, situating their actions within a discursive tradition that defies simplistic secular‑religious binaries.